Applying IoT sensor-based practices to enhance water/nutrient sustainability in potato production - Neocleous, Damianos; Stylianou, Andreas; Adamides, George; Omirou, Michalis; Sparaggis, Dionysis; Kaikiti, Kyriaki; Christou, Anastasis; Vassiliou, Loukia; Dalias, Panagiotis (Frontiers in Agronomy, 2025)
Efficient water and nutrient management are critical challenges for sustainable agriculture, particularly in water-scarce regions. This study was conducted in Kokkinochoria, Cyprus, with four replicates to account for field variability, to evaluate an IoT-connected, sensor-based ferti-irrigation tool (GS) in spring potato production compared with conventional practices (CL). The study provides clear, quantitative data on nitrogen and phosphorus potential losses along with key parameters related to water management. Results demonstrate that the GS approach reduced nitrogen (N) and phosphorus (P) potential losses by over 50%, significantly improved water productivity by 37%, and decreased overwatering by 84%. Despite reduced water/nutrient inputs, tuber yields under GS remained at a high range exceeding 50 t/ha, with no compromise in quality. Although yield per unit of nitrogen supplied remained consistent across treatments, the yield per unit of nitrogen lost varied, highlighting differences in environmental impacts among treatments. Sustainability indicators revealed that the GS approach reduced input costs and labor while increasing gross profit, without compromising yield. These findings contribute to better understanding of how agriculture is evolving IoT-based sensor practices to improve water/nutrient management and reduce their environmental impact in potato cropping systems, which is vital in water-scarce regions.